Research on precise positioning of shield roadheader robot system in coal mine - MA Hongwei; YANG Jinke; MAO Qinghua; WANG Qiang (Gong-kuang zidonghua, 2022)
At present, most of the positioning methods of underground tunneling equipment in coal mines adopt single auxiliary measurement methods such as machine vision, odometer and total station to combine with inertial navigation measurement to suppress the cumulative position error caused by inertial navigation solution over time. However, the single auxiliary measurement method is easy to be affected by the underground environment, and there are certain errors in position measurement, which leads to the reduction of the precision of the combined measurement method with inertial navigation. In order to solve the above problems, taking shield roadheader robot system in coal mine as the research object, a combined positioning method of strapdown inertial navigation+digital total station+displacement sensor is proposed. Firstly, the position and attitude angle parameters of the roadheader robot are calculated by using strapdown inertial navigation. Secondly, the position information of the roadheader robot measured by the digital total station and calculated by the displacement sensor are used to feedback and correct the position information calculated by the strapdown inertial navigation, so as to reduce the cumulative position error generated by the inertial navigation over time. Finally, the position and attitude angle information calculated by the strapdown inertial navigation, the position information obtained by the total station measurement and the position information estimated by the displacement sensor are fused by the multi-information fusion algorithm based on the federated filter, so as to obtain the accurate position and attitude information of the roadheader robot. The simulation and industrial experiment results show that the combined positioning method can well suppress the accumulative position solution errors of pure inertial navigation and realize the precise positioning of the shield roadheader robot in coal mines. The position errors in the x-axis and y-axis directions are controlled at ±0.03 m and ±0.02 m respectively, which meets the requirements of the underground driving face.